(untitled) (Acta Scientiarum. Biological Sciences, 2023)
The mobilization of an organism in response to noxious stimulation varies according to the degree of evolution of the nervous system, and the response, which is considered species-specific, depends on the type of noxious stimulus applied. Knowledge about the specific response of a species to a noxious stimulus is crucial to understanding the evolution of nocifensive responses and to providing information about the signals that can indicate discomfort or pain. The present study evaluated the behavioral and hormonal nociceptive responses of Oreochromis niloticus treated by subcutaneous injection of vehicle or formaldehyde 3% in the posterior region of the dorsal fin. Fish receiving formaldehyde injection spent less time with the soft ray dorsal fin moving and more time in a lowered position than vehicle-treated fish, and there was a negative correlation between these two variables in formaldehyde-treated fish. A skin-darkening pattern was identified in fish who died as a result of the noxious stimulus. The speed and distance traveled, plasma cortisol, body and eye darkening, and time spent with the spine ray dorsal fin erect were not significantly different between the treatments. The formaldehyde test activated the nociceptive system in O. niloticus and confirmed the hypothesis that the responses presented to this test are species-specific. In addition, the reduction of affected limb use (soft ray dorsal fin), similar to that observed in mammals submitted to the same test, indicates that pain sensation may be present in these animals.